Kebijakan Hukum Terhadap Perlindungan Tenaga Kerja yang Mengalami Kecelakaan Kerja - Surya Perdana (Inovasi, 2023)
This study discusses the legal policy of protection for workers who experience work accidents to find out legal protection and factors that prevent work accidents for workers. The research method used is normative law research. In accordance with the type and nature of the research, the data source used is secondary data consisting of primary legal materials in the form of Law No. 13 of 2003 concerning Manpower which was updated in Law No. 11 of 2020. Analysis of legal materials was carried out using the content analysis method. (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The results of the research obtained are how the legal protection for workers who experience work accidents and the legal protection efforts contained in the Manpower Act. The need for a labor protection policy is based on the fact that every worker faces various risks, both inside and outside of work. These risks have the potential to reduce the level of welfare of workers and their families. The policies carried out by the government in accordance with the manpower policy are to improve the welfare of the workers/laborers with various efforts including improving wages, social security, improving working conditions, in this case to improve the position and dignity of the workforce. Work accidents include risks from work, various risks that must be faced by workers in carrying out their work. To overcome the loss of part or all of the income caused by the existence of social risks such as death or disability due to work accidents, both physical and mental, it is necessary to have a work accident insurance.